Degradation and Rehabilitation: Conceptual Notes on the Notion of the Neighborhood - Vizcarra, Berenice (Corporación Universitaria del Caribe, CECAR., 2021)
The contemporary phenomenon of deterioration and abandonment of housing settlements forces the arbitrary implementation of urban and architectural projects, which do not always respond to the socio—cultural needs of the inhabitants. The following article aims to present a theoretical—conceptual approach, based on the analysis and evaluation of the degradation and rehabilitation processes in residential neighborhoods, supported by studies on Urban Planning, Urban Sociology and Sustainable Development. The result is intended to be a referential corpus that helps the application of alternatives in the face of increasing cases of loss of neighborhoods with patrimonial value.